Vascular aging and subclinical atherosclerosis: why such a “never ending” and challenging story in cardiology? - Iurciuc S (Dove Medical Press, 2017)
Stela Iurciuc,1,2 Anca Maria Cimpean,3 Florin Mitu,4 Rodica Heredea,5 Mircea Iurciuc1,2 1Department of Preventive Medicine, Angiogenesis Research Center, “Victor Babes” University of Medicine and Pharmacy, 2Clinical Emergency County Hospital “Pius Brînzeu,” 3Department of Microscopic Morphology/Histology, Angiogenesis Research Center, “Victor Babes” University of Medicine and Pharmacy, Timisoara, 4Department of Cardiology, “Grigore T Popa” University of Medicine and Pharmacy, Iasi, 5Department of Pathology, Louis Turcanu Children Hospital, Timisoara, Romania Abstract: The true onset of atherosclerosis remains one of the biggest challenges for cardiologists. Is atheroma plaque development considered the earliest step of vascular aging? If so, when it starts? Before or after birth? If it starts before birth or early during childhood, it seems that Thomas Sydenham was right: “A man is as old as his arteries.” Except disorganization of elastic fibers, less is known about the morphology of vascular aging and also about the molecular events influencing the age of arteries, arterial stiffness, and their role in the appearance of future complications. Cellular and molecular events responsible for the switch from physiologic to pathologic aging of human arteries are less known. Epigenetic, genetic, and environmental influences at the onset of early vascular aging (EVA) should specifically influence the process. This paper briefly reviews the controversial data regarding vascular aging with an emphasis on the less known facts about the morphology of EVA. Keywords: arterial stiffness, blood pressure variability, arterial aging, telomeres